Efforts to Increase Boil-Off Gas (BOG) Without Fuel Gas Pump in The State of Ballast Voyage at M.T. Coral Energy - Airlangga, Areza Putri; Sutoyo; Kusumawati, Elly; Firdaus, Imam (Journal of Engineering Science and Technology Management (JES-TM), 2026)
This study examines practical efforts to increase Boil-Off Gas (BOG) production without relying on the Fuel Gas Pump (FGP) during ballast voyage on the M.T. Coral Energy. In this condition, the vessel carries only a small amount of heel cargo, causing limited natural evaporation and a significant drop in tank pressure, which often results in insufficient BOG supply for the main engine. These operational constraints highlight the need for an alternative strategy that is both efficient and safer for cryogenic equipment.Using a qualitative descriptive approach, the research incorporates direct observation, structured interviews with deck officers, and operational documentation from the vessel. Data were analyzed using a fishbone framework to trace the root causes of low BOG production, focusing on technical, environmental, and human-factor aspects. The findings show that applying the top spray method using the deepwell pump effectively increases tank pressure and stabilizes BOG availability during ballast voyage. This method helps maintain a consistent gas supply for propulsion without adding mechanical load or maintenance risks to the FGP. The success of this approach depends largely on accurate flow control, careful pressure monitoring, and the crew’s understanding of the operational procedure. Overall, the study concludes that top spray is a reliable and energy-efficient alternative for BOG management when FGP use is minimized. The results are expected to support LNG carrier operations, particularly in optimizing fuel systems under low-cargo condition.